Lead by example: should sport take a stand against brands of unhealthy consumption?. (May 2016) - Flint, S.W.; Peake, R.
Highlights: Brands of unhealthy food and drink use sport to market their products. Brands of unhealthy food and drink use sport to target young people. Through association, sport is used to foster favourable perceptions of brands.